Restricted valency (NPNA) n repeats and junctional epitope-based circumsporozoite protein vaccines against Plasmodium falciparum - Mark D. Langowski; Farhat A. Khan; Sofya Savransky; Dallas R. Brown; Arasu Balasubramaniyam; William B. Harrison; Xiaoyan Zou; Zoltan Beck; Gary R. Matyas; Jason A. Regules; Robin Miller; Lorraine A. Soisson; et al. (npj Vaccines, 2022)
Abstract The Circumsporozoite Protein (CSP) of Plasmodium falciparum contains an N-terminal region, a conserved Region I (RI), a junctional region, 25–42 copies of major (NPNA) and minor repeats followed by a C-terminal domain. The recently approved malaria vaccine, RTS,S/AS01 contains NPNAx19 and the C-terminal region of CSP. The efficacy of RTS,S against natural infection is low and short-lived, and mapping epitopes of inhibitory monoclonal antibodies may allow for rational improvement of CSP vaccines. Tobacco Mosaic Virus (TMV) was used here to display the junctional epitope (mAb CIS43), Region I (mAb 5D5), NPNAx5, and NPNAx20 epitope of CSP (mAbs 317 and 580). Protection studies in mice revealed that Region I did not elicit protective antibodies, and polyclonal antibodies against the junctional epitope showed equivalent protection to NPNAx5. Combining the junctional and NPNAx5 epitopes reduced immunogenicity and efficacy, and increasing the repeat valency to NPNAx20 did not improve upon NPNAx5. TMV was confirmed as a versatile vaccine platform for displaying small epitopes defined by neutralizing mAbs. We show that polyclonal antibodies against engineered VLPs can recapitulate the binding specificity of the mAbs and immune-focusing by reducing the structural complexity of an epitope may be superior to immune-broadening as a vaccine design approach. Most importantly the junctional and restricted valency NPNA epitopes can be the basis for developing highly effective second-generation malaria vaccine candidates.